Monte Carlo calculations of drift velocities and diffusion coefficients of Ar+ ions in helium - Barata, J. A. S. (2007)
Results are presented for the calculated drift velocities and diffusion coefficients for Ar+ ions in helium at atmospheric pressure, temperature T=300 K and for reduced electric fields E/N from about 1 Td up to about 150 Td, using Monte Carlo techniques. The drift velocities range from 5.94×103 to 559.0×103 cm s-1 for the Ar+ ions in the ground state 2P3/2 and from 5.85×103 to 545.0×103 cm s-1 for the Ar+ ions in the metastable excited state 2P1/2. These values are in good agreement (within about 5%) with the few experimental values available. The mobilities and diffusion coefficients for atomic Ar+ ions in helium gas show no significant dependence on the spin state of the ion.